HUBUNGAN KETERPAPARAN MEDIA MASSA INTERNET DENGAN USIA MENARCHE PADA SISWI DENGAN STATUS GIZI LEBIH DI SMP NEGERI KECAMATAN PAUH KOTA PADANG TAHUN 2020 - Silvia Agustin Selvi; Nike Sari Oktavia; Alsri Windra Doni (STIKes MERCUBAKTIJAYA, 2020)
ABSTRACT In the last decade the age of menarche has shifted to a younger age. The age of the youngest menarche in Indonesia is 9 years with a prevalence of 15.3%. West Sumatera, 41,4% of young woman experience interest at the age of 13-4 years. Girls who experience menarche early are at risk of experiencing malignant disease, including cancer. Excessive nutrition and media exposure are factors that trigger early menarche. A preliminary survey of 10 respondents found that the age of early menarche was 6 students. out of 6, the internet media exposure was 2 people and 4 weight. The purpose of this study was to determine the relationship of internet mass media exposure to the age of menarche in female students with over nutritional status in State Junior High School, Pauh District, Padang City in 2020. This type of research is quantitative, analytic survey with cross sectional design. The study population was all female students with more nutritional status at SMPN 23 Padang and SMPN 14 Padang, Pauh District, Padang City with total sampling techniques, which fulfilled the sample questionnaire of 52 respondents. Then the data were analyzed univariately and bivariately with the Chi-Square statistical test. The results showed that 53.8% of respondents had exposure to heavy internet mass media, and 63.5% of respondents experienced early menarche age. The youngest menarche age is 10 years and the oldest is 14 years 7 months. The average age of menarche is 11.4 years. The relationship of internet mass media exposure with the age of menarche in students with more nutritional status with a p value of 0.027 (p <0.05). It can be concluded that there is a relationship between internet mass media exposure and the age of menarche in students with more nutritional status. It is hoped that the school will provide information about reproductive health regarding the impact of early menarche and direct students to use the internet on positive things. Keywords : Age of Menarche, Internet Mass Media Exposure, Over Nutritional Status. ABSTRAK Dalam dasawarsa terakhir usia menarche bergeser ke usia yang lebih muda. Usia menarche termuda di Indonesia adalah 9 tahun dengan prevelensi 15,3%. Sumatera Barat, 41,4% remaja putri mengalami menarche saat usia 13-14 tahun. Anak perempuan yang mengalami menarche dini beresiko mengalami penyakit keganasan, diantaranya penyakit kanker. Gizi yang berlebih dan keterpaparan media merupakan faktor pencetus menarche dini. Survei awal dari 10 responden didapatkan usia menarche dini sebanyak 6 siswi. Dari 6 siswi tersebut keterpaparan media massa internetnya sedang 2 orang dan berat 4 orang. Tujuan penelitian ini untuk mengetahui hubungan keterpaparan media massa internet dengan usia menarche pada siswi dengan status gizi lebih di SMP Negeri Kecamatan Pauh Kota Padang Tahun 2020. Jenis penelitian ini adalah kuantitatif, survei analitik dengan desain cross sectional. Populasi penelitian adalah seluruh siswi dengan status gizi lebih di SMPN 23 Padang dan SMPN 14 Padang Kecamatan Pauh Kota Padang dengan teknik total sampling, yang memenuhi kiriteria sampel sebanyak 52 orang responden. Kemudian data dianalisis secara univariat dan bivariat dengan uji statistik Chi-Square. Hasil penelitian didapatkan bahwa 53,8% responden memiliki keterpaparan media massa internet berat, dan 63,5% responden mengalami usia menarche dini. Usia menarche termuda adalah 10 tahun dan yang tertua adalah 14 tahun 7 bulan. Usia menarche rata-rata adalah 11,4 tahun. Hubungan keterpaparan media massa internet dengan usia menarche pada siswi dengan status gizi lebih dengan nilai p value 0,027 (p< 0,05). Dapat disimpulkan ada hubungan keterpaparan media massa internet dengan usia menarche pada siswi dengan status gizi lebih. Diharapkan pihak sekolah memberikan informasi tentang kesehatan reproduksi mengenai dampak menarche dini dan mengarahkan siswi untuk menggunakan internet pada hal yang positif. Kata kunci : Usia Menarche, Keterpaparan Media Massa Internet, Status Gizi Lebih.